PHILOSOPHICAL REVIEW OF THE IMPLEMENTATION OF CHINESE MUSLIM EDUCATION IN MAKASSAR CITY - ., Nuryamin (Jurnal Pendidikan Kreatif, 2022)
Education is a conscious effort made to improve the condition of individuals and society. If individuals and communities have awareness, a harmonious, harmonious and peaceful life will be created. Examining the development of Chinese Muslim education with a philosophical perspective on informal, formal and non-formal education. The three types of education will provide positive values ​​for Chinese Muslims to participate in the intellectual life of the nation. Observations and interviews as data collection instruments. The data analysis technique is data reduction by organizing and organizing data, presenting data and verifying data, then drawing conclusions with a philosophical rational approach to the research focus. The results obtained: 1. Informal education runs as informal education for Muslim communities in general. Epistemologically, the Chinese Muslim community develops scientific structures, including religious sciences and general sciences 2. The formal education presented by the Chinese Muslim community includes kindergartens, and there are also universities with built scientific structures, namely empirical science as a response to the development of science and technology. The College of Management and Computer Science was founded by a Chinese Muslim whose curriculum content is to strengthen prospective graduates to master science and technology. 3. Non-formal education: a). Pondok Tahfidzul Qur'an is the takmir program of the Muhammad Cheng Hoo mosque. b). Training of converts. c). Community development is like dhikr together every Friday night. d). Routine assessment twice a week. The Teonghoa Muslim education movement philosophically instills religious values ​​that are embraced by both the Chinese Muslim community and the Muslim community in Makassar City.